Feasibility Test of Case Study Oriented Textbooks in Educational Digital Psychology Courses - Desfaur Natalia; Dara Mutiara Aswan; Mia Aina (Postgraduate, University of Mataram, 2025)
This study aims to test the feasibility of a case study-oriented textbook in the course of educational digital psychology. This research is an R&D study using the ADDIE development model. The study was conducted on 2nd semester biology students in the Biology Education Study Program, University of Jambi. The instruments used were expert validation questionnaires, lecturer and student response questionnaires on the quality of the book. The data analysis techniques used were expert validity score tests and student response questionnaire scores. In the validity test, the results of the study showed that the developed textbook was very feasible to be used in learning activities with a percentage score of 95% in terms of material feasibility, and 90% in terms of media feasibility. So, from the results of the expert assessment, it can be concluded that the case study-oriented textbook in the Educational Digital Psychology course is very feasible to be used in learning activities.